Heat-conducting sheath elastomer material applied to new energy charging cable
By constructing a three-dimensional thermally conductive network with adaptive wetting and microscopic self-healing through BNNS/C-paraffin composite filler, the problems of poor thermal conductivity and material durability in new energy charging cables are solved, achieving a balance between efficient heat dissipation and flexibility.
Patent Information
- Application Number
- CN202511844091.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-01-23
AI Technical Summary
The sheathing material of existing new energy charging cables has poor thermal conductivity, which leads to heat accumulation, affects service life and poses safety hazards. In addition, the high filler ratio increases the material hardness and reduces flexibility, making it unable to maintain thermal conductivity under dynamic stress.
By using BNNS/C-paraffin composite filler and through multi-level structural design and intelligent phase change materials, a three-dimensional heat conduction network with adaptive wetting and microscopic self-healing is constructed. The phase change of paraffin forms liquid bridges at the interface, which improves heat conduction efficiency and repairs microscopic damage.
It significantly improves the thermal conductivity and mechanical durability of charging cables, providing a highly efficient, reliable, and flexible solution that adapts to the stability of materials under dynamic stress.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of high polymer composite materials, and particularly relates to a heat-conducting sheath elastomer material applied to a new energy charging cable. BACKGROUND
[0002] With the global energy structure transforming towards green and low carbon, the new energy vehicle industry is developing rapidly. In order to alleviate the range anxiety of users and improve the use experience, shortening the charging time has become the core competitiveness of the industry, which makes the high-power super charging technology (such as 800kW and above) an inevitable trend. According to Joule's law, during the charging process, a large amount of heat will be generated in the cable conductor due to the resistance effect, and the charging power is proportional to the square of the current, resulting in the rapid accumulation of heat. The continuous high temperature environment will accelerate the thermal oxidative aging of the cable insulation layer and the sheath high polymer material, causing the material to become hard and brittle, the mechanical properties to decrease, and ultimately the service life of the cable to be shortened, and the safety hazards of melting, short circuit and even fire to be buried.
[0003] To cope with this challenge, the most popular high-efficiency heat dissipation scheme at present is to integrate a liquid cooling system inside the charging cable. However, the efficiency of this system is limited by a key bottleneck: the material of the cable conductor sheath is mostly high polymer such as thermoplastic polyurethane (TPU), thermoplastic elastomer (TPE), etc., which are essentially poor conductors of heat. This results in the heat generated in the internal conductor of the cable being unable to be effectively transferred to the external liquid cooling circulation system through the sheath.
[0004] The existing technology generally uses high thermal conductivity insulating fillers such as boron nitride (boron nitride nanosheet BNNS), aluminum oxide, etc. to fill the polymer matrix to improve the thermal conductivity of the sheath. However, this method has inherent and difficult-to-overcome drawbacks: first, although the fillers themselves have high thermal conductivity, they are randomly distributed in the form of isolated points and lines in the matrix, and it is difficult to form a continuous and efficient three-dimensional heat conduction network, so the heat conduction efficiency is greatly reduced. Second, in order to improve the dispersibility of the fillers and enhance the interfacial compatibility with the polymer, the fillers are often surface modified using silane coupling agents, etc. Although this increases the contact probability of the fillers, these organic modifiers themselves have very poor thermal conductivity, and will form an additional phonon scattering barrier at the filler interface, which will weaken the overall heat conduction ability.
[0005] In order to achieve the expected thermal conductivity performance, the existing technology has to greatly increase the filling proportion of the fillers. This high filling amount will severely damage the movement of the high molecular chain segments, causing the hardness of the composite material to increase significantly and the flexibility to decrease sharply, making the charging cable heavy and rigid, and the user experience poor. More seriously, under the frequent dynamic stress such as dragging and bending of the new energy charging cable, the filler particles in the high filling system and the polymer matrix are prone to interfacial peeling, producing microcracks, not only causing the thermal conductivity performance to deteriorate rapidly, but also possibly leading to the cracking of the sheath structure and the loss of its basic protection function. SUMMARY
[0006] In order to solve the technical problems mentioned in the background art, the purpose of the present application is to provide a heat-conducting sheath elastomer material applied to new energy charging cables.
[0007] The purpose of the present application can be achieved by the following technical solutions: A heat-conducting sheath elastomer material applied to new energy charging cables, the specific components are: BNNS / C-paraffin composite filler 25-33wt%, auxiliary heat-conducting filler 9-13wt%, lubricant 1.2-1.5wt%, and antioxidant 0.15-0.2wt%, and the balance is TPE resin; the preparation method is: TPE resin, lubricant and antioxidant are fed from the main feeding port, BNNS / C-paraffin composite filler and auxiliary heat-conducting filler are mixed and then fed from the side feeding port, and then melt blending, extrusion and granulation to obtain the heat-conducting sheath elastomer material.
[0008] Preferably, the auxiliary heat-conducting filler is spherical aluminum oxide with an average particle size of 1-5μm.
[0009] The preparation method of the BNNS / C-paraffin composite filler is: Step A1: premix alkyl alcohol, triethylamine and tetrahydrofuran, cool to below 10℃, slowly add diphenylvinyl chlorosilane under dry nitrogen atmosphere, stir for 0.5-0.8h, then warm up to reflux for 1.5-2h, filter and recover tetrahydrofuran by rotary evaporation, wash the substrate with ethanol to obtain an intermediate; Further, the amount ratio of diphenylvinyl chlorosilane, alkyl alcohol, triethylamine and tetrahydrofuran is 0.1mol:0.11-0.12mol:10-15mL:270-330mL, and the active chlorosilane group of alkyl alcohol and diphenylvinyl chlorosilane is substituted; Preferably, the alkyl alcohol is C10-C16 alkyl alcohol, which is easy to form uniform carbon wool at high temperature.
[0010] Step A2: premix the intermediate, 3-mercapto propyl triethoxysilane and dioxane, add a photoinitiator 369 and mix, irradiate under ultraviolet light at 30-35mW / m 2 Stir for 6-8h under ultraviolet irradiation, recover dioxane by rotary evaporation to obtain a modifier; Further, the amount ratio of the intermediate, 3-mercapto propyl triethoxysilane, photoinitiator 369 and dioxane is 0.1mol:0.1mol:40-55mg:200-250mL, and the mercapto-alkene click addition reaction of 3-mercapto propyl triethoxysilane and the vinyl structure of the intermediate is carried out.
[0011] Step A3: the modifier and dimethylacetamide aqueous solution are premixed, heated to 50-70 DEG C, hydrolyzed for 1-1.3 h under stirring, after adding boron nitride nanosheet ultrasonic dispersion, standing for 12 h, centrifugation, drying the precipitate, then oxygen-free carbonization roasting, cooling to obtain the composite carrier; Further, the amount ratio of boron nitride nanosheet, modifier and dimethylacetamide aqueous solution is 50 g:8.2-10.5 g:300-380 mL, the triethoxysilane structure in the modifier molecule is hydrolyzed and coupled with the boron nitride nanosheet to be loaded; Further, the oxygen-free carbonization roasting adopts two-stage roasting process, the first stage roasting temperature is 480-520 DEG C, the time is 2-2.5 h, the second stage roasting temperature is 800-850 DEG C, the time is 1-1.3 h.
[0012] Step A4: the composite carrier is immersed in molten paraffin, hot filtration is controlled to control the paraffin loading amount to be 12-18 wt%, air cooling is performed to shape, and the BNNS / C-paraffin composite filler is obtained. Further, the melting temperature of the paraffin is 60-70 DEG C.
[0013] The beneficial effects of the present application are as follows: The core advantage of the heat-conducting sheath elastomer material provided by the present application is derived from the unique "self-adaptive infiltration, micro self-repairing" three-dimensional heat-conducting network constructed by the BNNS / C-paraffin composite filler. The filler solves the problems of discontinuous heat-conducting path and interface failure in the traditional technology from the root by the multi-level structure design.
[0014] Firstly, the composite filler forms a unique "sandwich" layered structure through controllable chemical synthesis and heat treatment. The preparation starts from grafting a specially designed silicone modifier on the surface of boron nitride nanosheet (BNNS). Then, during the oxygen-free roasting process, the organic layer undergoes precise pyrolysis conversion: the siloxane part adjacent to BNNS is converted into a layer of firm and thermal expansion coefficient matched amorphous silicon carbon layer, and the intermediate layer ensures the firmness and thermal stability of the interface bonding through strong chemical bonding with BNNS; and the external long-chain alkyl and benzene ring are decomposed into a carbon layer with a fluff shape. This multi-level structure of "BNNS core-amorphous silicon carbon intermediate layer-carbon fluff outer shell" is the functional basis for realizing efficient and stable heat conduction.
[0015] Secondly, the structure cooperates with paraffin to realize the "dynamic self-adaptation" and "micro repair" of the heat-conducting network. The carbon fluff structure of the outer layer of the composite filler has a large specific surface area and strong capillary action, which can firmly load and lock the phase change paraffin in its interior and surface, preventing its migration in long-term use. When the cable works and the temperature rises to the melting point of paraffin, the solidified paraffin melts into liquid, forming a dynamic "liquid bridge" between adjacent composite filler particles.
[0016] This liquid bridge effect brings two core advantages: Efficient construction of heat conduction path: liquid paraffin can instantly infiltrate and fill the microscopic gaps between fillers, converting unstable point contact into large-area surface contact, significantly reducing interface thermal resistance, and thus achieving effective leap in heat conduction performance.
[0017] Repairing interface micro-damage: when the material produces microscopic cracks due to repeated bending or the filler-matrix interface undergoes slight peeling, the flowing paraffin can infiltrate these defect areas under capillary driving, playing the role of "liquid phase repair", re-bridging the heat conduction path, and thus maintaining the long-term stability of the heat conduction network.
[0018] In summary, by combining the multi-level structure design of BNNS / C-paraffin composite filler with intelligent phase change material, the present application not only significantly improves the heat conduction efficiency of the sheath material, but also endows it with excellent mechanical durability, providing an ideal solution for high-power new energy charging cables with high-efficiency heat dissipation, long-term reliability and excellent flexibility. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application will be described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of the present application.
[0020] Example 1, preparation of heat-conducting sheath elastomer material, the specific implementation method is as follows: I. Preparation of BNNS / C-paraffin composite filler Step A1: Take C10 alcohol (decyl alcohol), triethylamine and tetrahydrofuran, stir and pre-mix, cool the reaction system to 10℃ using an ice water bath, protect with dry nitrogen gas, slowly add diphenylvinyl chlorosilane and stir for 0.5h, then heat to 65℃ and reflux for 1.5h, wherein the amount ratio of diphenylvinyl chlorosilane, C10 alcohol, triethylamine and tetrahydrofuran is 0.1mol:0.11mol:10mL:270mL, then filter to remove salt, recover tetrahydrofuran by rotary evaporation, wash the substrate with ethanol, and separate ethanol to obtain the intermediate.
[0021] Step A2: Take the intermediate, 3-mercaptopropyl triethoxysilane and dioxane, stir and pre-mix, add photoinitiator 369 and mix evenly, irradiate with a 365nm ultraviolet light source, control the irradiation intensity to be 30mW / m 2And stirring reaction 8h, wherein, the intermediate, 3-mercapto propyl triethoxysilane, photoinitiator 369 and dioxane dosage ratio is 0.1mol:0.1mol:40mg:200ml, after recovery dioxane by rotary evaporation, the modifier is obtained.
[0022] Step A3: prepare a 60% volume fraction of dimethylacetamide aqueous solution, pre-mix the modifier and dimethylacetamide aqueous solution, heat to 50℃ and stir for 1.3h, add boron nitride nanosheet (commercial powder, sheet diameter 1-3μm) and ultrasonic dispersion, then stand for 12h, wherein the dosage ratio of boron nitride nanosheet, modifier and dimethylacetamide aqueous solution is 50g:9g:320ml, then centrifuge and dry the precipitate, place the dry powder in a nitrogen atmosphere furnace, and perform two-stage calcination for anaerobic carbonization, with parameters set as: one-stage calcination temperature 480℃, time 2.5h, two-stage calcination temperature 800℃, time 1.3h, and after cooling, the composite carrier is obtained.
[0023] Step A4: take paraffin (commercial raw material, melting temperature 64-68℃) and heat to 80℃ to completely melt, immerse the composite carrier, vacuum filter, and heat filter the filtrate at 72℃ to precipitate the surface residual paraffin, control the paraffin loading amount to be 12wt%, and after reaching the loading amount, perform air cooling to shape, to obtain the BNNS / C-paraffin composite filler.
[0024] II. Melt blending and granulation According to the weight percentage, take the raw materials: BNNS / C-paraffin composite filler 25wt%, made by the embodiment; auxiliary heat-conducting filler 13wt%, select spherical aluminum oxide powder, model CY-L15; lubricant 1.2wt%, select commercially available zinc stearate; antioxidant 0.2wt%, select antioxidant 1010 and antioxidant 168 mixed in equal weight ratio; the rest is TPE resin, use Telcar®TL-1934F type resin raw material.
[0025] Mix the above TPE resin, lubricant and antioxidant, and then feed from the main feeding port of the twin-screw extruder, mix the BNNS / C-paraffin composite filler and auxiliary heat-conducting filler, and then feed from the side feeding port, set the extruder barrel temperature as: zone 1 175℃, zone 2 190℃, zone 3 200℃, zone 4 210℃, melt blend and extrude granulation of the components, to obtain the heat-conducting sheath elastomer material.
[0026] Example 2, prepare the heat-conducting sheath elastomer material, the specific implementation method is as follows: I. Preparation of BNNS / C-paraffin composite filler Step A1: Take C10 alcohol (decyl alcohol), triethylamine and tetrahydrofuran as raw materials, stir and mix, cool the reaction system to 10°C with an ice water bath, protect with dry nitrogen, slowly add diphenylvinylchlorosilane, stir for 0.5h, then heat to 65°C and reflux for 1.7h, wherein the amount ratio of diphenylvinylchlorosilane, C10 alcohol, triethylamine and tetrahydrofuran is 0.1mol:0.11mol:12mL:290mL, then filter out the salt, recover tetrahydrofuran by rotary evaporation, wash the substrate with ethanol, and separate ethanol to obtain the intermediate.
[0027] Step A2: Take the intermediate, 3-mercaptopropyl triethoxysilane and dioxane, stir and mix, add a photoinitiator 369, mix well, and irradiate with a 365nm ultraviolet light source, control the irradiation intensity at 30mW / m 2 and stir for 7.5h, wherein the amount ratio of the intermediate, 3-mercaptopropyl triethoxysilane, photoinitiator 369 and dioxane is 0.1mol:0.1mol:45mg:200mL, then recover dioxane by rotary evaporation to obtain the modifier.
[0028] Step A3: Prepare a 60% volume fraction dimethylacetamide aqueous solution, pre-mix the modifier and the dimethylacetamide aqueous solution, heat to 55°C, stir and hydrolyze for 1.3h, add boron nitride nanosheets (commercial powder, sheet diameter 1-3μm) and ultrasonic dispersion, then stand for 12h, wherein the amount ratio of boron nitride nanosheets, modifier and dimethylacetamide aqueous solution is 50g:8.2g:300mL, then centrifuge, take the precipitate and dry, place the dry powder in a nitrogen atmosphere furnace, perform two-stage roasting for anaerobic carbonization roasting, parameter settings: one-stage roasting temperature is 500°C, time is 2h, two-stage roasting temperature is 800°C, time is 1.3h, cool to obtain the composite carrier.
[0029] Step A4: Take paraffin (commercial raw material, melting temperature is 64-68°C), heat to 80°C to completely melt, immerse in the composite carrier, vacuum suction filtration, filter the residue, heat filter at 72°C to precipitate the surface residual paraffin, control the paraffin loading amount to be 15wt%, after reaching the loading amount, air cooling to shape, to obtain the BNNS / C-paraffin composite filler.
[0030] II. Melt blending granulation According to the weight percentage, take the raw materials: BNNS / C-paraffin composite filler 28wt%, made by the embodiment; auxiliary heat-conducting filler 12wt%, select spherical aluminum oxide powder, model CY-L15; lubricant 1.3wt%, select commercially available zinc stearate; antioxidant 0.17wt%, select antioxidant 1010 and antioxidant 168 mixed in equal weight ratio; the rest is TPE resin, use Telcar®TL-1934F type resin raw material.
[0031] The above TPE resin, lubricant and antioxidant were mixed and fed from the main feeding port of the twin-screw extruder, and the BNNS / C-paraffin composite filler and auxiliary heat-conducting filler were mixed and fed from the side feeding port. The barrel temperature of the extruder was set as follows: Zone 1, 175°C; Zone 2, 190°C; Zone 3, 200°C; and Zone 4, 210°C. The components were melt blended and extruded to obtain the heat-conducting sheath elastomer material.
[0032] Example 3, preparation of a heat-conducting sheath elastomer material, the specific implementation method is as follows: I. Preparation of BNNS / C-paraffin composite filler Step A1: C16 alcohol (hexadecanol), triethylamine and tetrahydrofuran were stirred and pre-mixed. The reaction system was cooled to 10°C using an ice water bath, dry nitrogen was introduced for protection, and diphenylvinyl chlorosilane was slowly added and stirred for 0.8h. Then the temperature was increased to 65°C and refluxed for 1.8h. The amount ratio of diphenylvinyl chlorosilane, C16 alcohol, triethylamine and tetrahydrofuran was 0.1 mol: 0.12 mol: 15 mL: 330 mL. Then the salt was removed by filtration, and the tetrahydrofuran was recovered by rotary evaporation. The substrate was washed with ethanol, and the ethanol was separated to obtain the intermediate.
[0033] Step A2: The intermediate, 3-mercaptopropyl triethoxysilane and dioxane were stirred and pre-mixed, and the photoinitiator 369 was added and mixed. The irradiation was performed using a 365nm ultraviolet light source, and the irradiation intensity was controlled at 35mW / m 2 and stirred for 6h. The amount ratio of the intermediate, 3-mercaptopropyl triethoxysilane, photoinitiator 369 and dioxane was 0.1 mol: 0.1 mol: 55 mg: 250 mL. Then the dioxane was recovered by rotary evaporation to obtain the modifier.
[0034] Step A3: A dimethylacetamide aqueous solution with a volume fraction of 60% was prepared, and the modifier and the dimethylacetamide aqueous solution were pre-mixed. The temperature was increased to 70°C and hydrolyzed for 1h. The boron nitride nanosheet (commercial powder with a sheet diameter of 1-3μm) was ultrasonically dispersed and then left to stand for 12h. The amount ratio of the boron nitride nanosheet, the modifier and the dimethylacetamide aqueous solution was 50g: 9.5g: 380mL. Then the precipitate was centrifuged and dried. The dried powder was placed in a nitrogen atmosphere furnace, and two-stage roasting was performed for anaerobic carbonization roasting. The parameters were set as follows: the first-stage roasting temperature was 520°C, and the time was 2h. The second-stage roasting temperature was 850°C, and the time was 1h. After cooling, the composite carrier was obtained.
[0035] Step A4: The paraffin wax (commercial raw material, melting temperature 64-68°C) was heated to 80°C to completely melt, and then immersed in the composite carrier. The filter was vacuum filtered, and the surface residual paraffin wax was separated by hot filtration at 72°C. The paraffin wax loading was controlled at 18wt%. After reaching the loading, air cooling was performed to shape, and the BNNS / C-paraffin wax composite filler was obtained.
[0036] II. Melt blending and granulation The raw materials were taken according to the weight percentage: 33wt% of BNNS / C-paraffin wax composite filler, which was prepared by the present example; 9wt% of auxiliary heat-conducting filler, which was selected as spherical aluminum oxide powder with model CY-L15; 1.5wt% of lubricant, which was selected as commercially available zinc stearate; 0.15wt% of antioxidant, which was selected as a mixture of antioxidant 1010 and antioxidant 168 in equal weight ratio; and the balance was TPE resin, which adopted Telcar® TL-1934F type resin raw material.
[0037] After mixing the above TPE resin, lubricant and antioxidant, the main feeding of the twin-screw extruder was fed. The BNNS / C-paraffin wax composite filler and the auxiliary heat-conducting filler were mixed and fed from the side feeding port. The barrel temperature of the extruder was set as follows: Zone 1 175°C, Zone 2 190°C, Zone 3 200°C, Zone 4 210°C. The components were melt blended and extruded to obtain the heat-conducting sheath elastomer material.
[0038] Example 4, preparation of heat-conducting sheath elastomer material, the specific implementation method is as follows: I. Preparation of BNNS / C-paraffin wax composite filler Step A1: C16 alcohol (hexadecanol), triethylamine and tetrahydrofuran were pre-mixed by stirring. The reaction system was cooled to 10°C using an ice water bath, dry nitrogen was introduced for protection, and diphenylvinyl chlorosilane was slowly added for stirring for 0.8h. Then the temperature was increased to 65°C for refluxing for 2h. The amount ratio of diphenylvinyl chlorosilane, C10 alcohol, triethylamine and tetrahydrofuran was 0.1mol:0.12mol:13mL:320mL. Then the salt was removed by filtration, and the tetrahydrofuran was recovered by rotary evaporation. The substrate was washed with ethanol, and the ethanol was separated to obtain the intermediate.
[0039] Step A2: The intermediate, 3-mercaptopropyl triethoxysilane and dioxane were pre-mixed by stirring, and the photoinitiator 369 was added and uniformly mixed. The irradiation was performed using a 365nm ultraviolet light source, and the irradiation intensity was controlled at 35mW / m 2 and stirring for 6.5h. The amount ratio of the intermediate, 3-mercaptopropyl triethoxysilane, photoinitiator 369 and dioxane was 0.1mol:0.1mol:50mg:250mL. Then the dioxane was recovered by rotary evaporation to obtain the modifier.
[0040] Step A3: prepare a 60% volume fraction aqueous dimethylacetamide solution, pre-mix the modifier and the aqueous dimethylacetamide solution, stir and hydrolyze at 65°C for 1.1 h, add boron nitride nanosheets (commercially available powder, flake diameter 1-3 μm) after ultrasonic dispersion and stand for 12 h, wherein the amount ratio of the boron nitride nanosheets, the modifier and the aqueous dimethylacetamide solution is 50 g: 10.5 g: 380 mL, then centrifuge to take the precipitate and dry, place the dried powder in a nitrogen atmosphere furnace, perform two-stage roasting for anaerobic carbonization roasting, and set the parameters as follows: one-stage roasting temperature is 510°C, time is 2.5 h, two-stage roasting temperature is 830°C, time is 1.1 h, and after cooling, the composite carrier is obtained.
[0041] Step A4: melt paraffin wax (commercially available raw material, melting temperature is 64-68°C) at 80°C to complete melting, immerse the composite carrier, vacuum suction filter, and perform hot filtration of the filtrate at 72°C to precipitate the surface residual paraffin wax, control the paraffin wax loading amount to be 15 wt%, and after reaching the loading amount, perform air cooling to shape, to obtain the BNNS / C-paraffin wax composite filler.
[0042] II. Melt blending and granulation Take the raw materials according to the weight percentage: 30 wt% of the BNNS / C-paraffin wax composite filler, which is self-made in this example; 11 wt% of the auxiliary heat-conducting filler, which is selected to be spherical aluminum oxide powder with a model number of CY-L15; 1.4 wt% of the lubricant, which is selected to be commercially available zinc stearate; 0.18 wt% of the antioxidant, which is selected to be a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio; and the balance is TPE resin, which is Telcar® TL-1934F type resin raw material.
[0043] After mixing the above TPE resin, lubricant and antioxidant, the TPE resin is fed from the main feeding port of the twin-screw extruder, the BNNS / C-paraffin wax composite filler and the auxiliary heat-conducting filler are mixed and fed from the side feeding port, and the extruder barrel temperature is set as follows: zone 1 175°C, zone 2 190°C, zone 3 200°C, and zone 4 210°C, to melt blend and extrude granulation of the components, to obtain the heat-conducting sheath elastomer material.
[0044] Comparative Example 1: refer to Example 4, replace the BNNS / C-paraffin wax composite filler with 25.5 wt% of boron nitride nanosheets and 4.5 wt% of paraffin wax, melt mix and cool to shape, and then add, and the rest of the implementation method is completely the same.
[0045] Comparative Example 2: based on Comparative Example 1, increase the amount of boron nitride nanosheets to 38 wt%, adjust the balance to 100 wt% by TPE resin, and the rest is completely the same.
[0046] The elastomer material prepared above was hot-pressed into a sheet-shaped sample at 180℃, 10MPa, and the thermal conductivity was detected at 25℃, 50℃, 70℃ and 80℃ respectively according to the standard of ASTM D5470-24; the specific detection results are shown in Table 1: Table 1 Thermal conductivity detection results of the initial sample at different temperatures
[0047] Note: The unit of thermal conductivity in Table 1 is W / (m·K).
[0048] The sheet-shaped sample prepared above was taken for bending test, specifically: the sheet sample was fixed on the bending tester, and repeated bending was carried out on a cylinder with a radius of 5 times the outer diameter of the sheath (42mm general cable) at a frequency of 30 times per minute for 1000 times, and the thermal conductivity was detected again at 70℃ and compared with the detection results in Table 1 to calculate the change rate; the specific test results are shown in Table 2: Table 2 Thermal conductivity detection results of the sample after bending at 70℃
[0049] Note: In Table 2, λ is the thermal conductivity, and the unit is W / (m·K); Δ is the change rate, and the unit is %.
[0050] From the above detection results, it can be seen that the elastomer material prepared in the examples has a higher thermal conductivity, and the thermal conductivity increases significantly at about 70℃, and after analysis, it is possible that the paraffin in the carbon wool surface layer of the BNNS / C-paraffin composite filler is melted and infiltrated to connect the filler, and a high-efficiency heat conduction network is constructed. In the simulation bending test, the change rate of the thermal conductivity of the example is significantly lower than that of the comparative example, especially the high filler content of Comparative Example 2, which shows stable heat conduction capacity.
[0051] In the description of the specification, the description of the reference terms "one embodiment", "example", "specific example" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are contained in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0052] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements or use similar ways to replace the described specific embodiments, as long as they do not deviate from the scope of the invention or exceed the scope defined by the present claims, which shall belong to the protection scope of the present application.
Claims
1. A heat conductive jacket elastomeric material applied to a new energy charging cable, characterized in that, The specific components are: BNNS / C-paraffin composite filler 25-33wt%, auxiliary heat-conducting filler 9-13wt%, lubricant 1.2-1.5wt%, and antioxidant 0.15-0.2wt%, and the rest is TPE resin; The preparation method of the BNNS / C-paraffin composite filler is: Step A1: premixing alkyl alcohol, triethylamine and tetrahydrofuran, slowly adding diphenylvinyl chlorosilane under cooling conditions and dry nitrogen atmosphere, stirring for 0.5-0.8h, then heating to reflux for 1.5-2h to prepare an intermediate; Step A2: Intermediate, 3-mercaptopropyltriethoxysilane and dioxane were premixed, light initiator 369 was added and mixed well, and the mixture was irradiated under UV light at 30-35 mW / m 2 The reaction was stirred under UV irradiation for 6-8 h to produce the modifier. Step A3: premixing the modifier and dimethylacetamide aqueous solution, stirring for hydrolysis at 50-70℃ for 1-1.3h, adding boron nitride nanosheet and ultrasonic dispersion, then standing for 12h, and baking the precipitated oxygen-free carbon to prepare a composite carrier; Step A4: immersing the composite carrier in molten paraffin, hot filtering to control the paraffin loading amount to be 12-18wt%, and air cooling to shape to obtain the BNNS / C-paraffin composite filler.
2. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to claim 1, characterized in that, The amount ratio of diphenylvinyl chlorosilane, alkyl alcohol, triethylamine and tetrahydrofuran is 0.1mol:0.11-0.12mol:10-15mL:270-330mL.
3. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to claim 2, characterized in that, The alkyl alcohol is C10-C16 alkyl alcohol.
4. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to claim 2, characterized in that, The amount ratio of the intermediate, 3-mercaptopropyl triethoxysilane, photoinitiator 369 and dioxane is 0.1mol:0.1mol:40-55mg:200-250mL.
5. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to claim 4, characterized in that, The amount ratio of boron nitride nanosheet, modifier and dimethylacetamide aqueous solution is 50g:8.2-10.5g:300-380mL.
6. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to claim 5, characterized in that, The oxygen-free carbon baking adopts a two-stage baking process, the first stage baking temperature is 480-520℃, and the time is 2-2.5h, the second stage baking temperature is 800-850℃, and the time is 1-1.3h.
7. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to claim 5, characterized in that, The melting temperature of paraffin is 60-70℃. 8.The heat-conducting sheath elastomeric material applied to a new energy charging cable according to claim 1, characterized in that, The auxiliary heat-conducting filler is spherical alumina with an average particle size of 1-5μm.
9. The heat-conducting sheath elastomeric material applied to the new energy charging cable according to any one of claims 1-8, characterized in that, The preparation method of the heat-conducting sheath elastomer material is: feeding TPE resin, lubricant and antioxidant from the main feeding port, mixing BNNS / C-paraffin composite filler and auxiliary heat-conducting filler, and feeding from the side feeding port, melt blending, extruding and granulating to obtain the heat-conducting sheath elastomer material.
Citation Information
Patent Citations
Low-thermal-resistance phase change heat conduction material and preparation method thereof
CN120988482A